Effects of allicin supplementation on exercise-induced muscle damage, IL-6, and antioxidative capacity - Su, Q. S.; Tian, Y.; Sun, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: A double-blinded, placebo-controlled study was conducted in well-trained athletes. The purpose was to investigate the effects of allicin supplementation on exercise-induced muscle damage (EIMD), interleukin-6(IL-6) and antioxidative capacity. Methods Subjects were randomly assigned to an allicin supplementation group (AS group) and a control group, and received either allicin or placebo for 14 days before and 2 days after a downhill treadmill run. Plasma creatine kinase (CK), CK-MM, lactate dehydrogenase (LDH), IL-6, superoxide dismutase (SOD), total antioxidative capacity (TAC) and perceived muscle soreness were measured pre and post exercise. Results Results indicated the AS group had significantly lower plasma levels of CK, CK-MM and IL-6, and reduced perceived muscle soreness after exercise, when compared with the control group. The AS group also demonstrated a trend toward reducing plasma level of LDH after exercise (P=0.08), although not statistically significant. Allicin supplementation induced a higher value of TAC at rest, and this higher value was maintained 48 h after exercise, however, there was no difference in SOD values after exercise between the two groups. Discussion / Conclusions The results suggested that allicin might be a potential agent to reduce EIMD. Further studies concerning anti-inflammatory and anti-oxidative effects of allicin on EIMD are needed.